Cross-cultural competencies in public management, the concept of training and competencies in the public sector, the role of national schools in Balkans - Resuli, Vebina; Lamcja, Dhurata (Edelweiss Applied Science and Technology, 2024)
The increasing cultural and linguistic variety in academic contexts needs higher cultural competence on the part of instructors, which necessitates a better knowledge of both teachers' levels of cultural competence and the experiences that develop cultural competence. Cross-cultural communication is critical for avoiding cross-cultural shocks and cross-cultural interaction, which promotes the formation of new elements and forms of cultural activity, as well as the adjustment of value orientations, behavioral models, and lifestyle (universal and culturally unique components). Cross-cultural competencies have become increasingly important in public management due to the rising globalization and diversity of societies. In the Balkans region, where different cultures and languages exist, the development of cross-cultural competencies is critical for effective public management. National schools have been identified as crucial institutions for developing these competencies. The method used in this study we have used empirical studies with specific variables in order to find out more about the cross-cultural competencies in public management. The literature review method involves a systematic and rigorous approach to identifying and analyzing relevant academic sources to comprehensively understand a research area. National schools in the Balkans have a critical role to play in developing cross-cultural competencies in public management. Teaching and learning must integrate global perspective education so that students may become responsible "active" global citizens. Global/international education must start with an attempt to comprehend globalization. Furthermore, cross-cultural experiences in teacher education may foster cultural competency, cooperation skills, and an understanding of global linkages, which can then be transferred to the classroom. Rethinking teaching and learning in these ways may give us the chance to gain a deeper knowledge and appreciation for people throughout the world, which is crucial to our duties and obligations as global citizens.